Quality of Verbal communication of health care team with hospitalized children under 3 - Godarzi, Z; Darvish, A; Nilli, F; Khushabi, K; Mehran, A; Nori Kermanshahi, S; Tabari, F; Vaskoei, kh; Naji, T; Ghodosi, R (Advances in Nursing & Midwifery, 2010)
Background and aim For different reasons, children may experience hospitalization. With respect to the importance of human relationships and verbal communication in this group for creating confidence and a sense of security with healthcare team, this descriptive study was conducted to identify the quality of verbal communication of the team with hospitalized children under 3 in 2008. Materials and methods 253 nurses and 87 physicians working in pediatric wards of hospitals affiliated to Tehran University of Medical Sciences took part. Data collection tools included a demographic questionnaire and a verbal communication checklist in 3 levels: good, moderate and poor. The checklist was designed for 2 age groups (0-1 and 1-3) to evaluate age differences and communication needs more accurately. Chi-square and exact Fisher tests were used for data analysis. Data were analyzed by SPSS 11. Findings %41.9 and %60.8 of nurses had poor communication with children 0-1 and 1-3 respectively. %42.3 of head nurses had good communication with children 0-1 and 1-3. %38.4 and %48.9 of physicians had good communication with children 0-1 and 1-3 respectively. A significant correlation was found between the verbal communication quality of nurses and such demographic variables as having children, educational level and shift time as well as of head nurses and educational level (P<0.05). Conclusion According to findings, verbal communication quality of most nurses with children under 3 was poor while most head nurses and physicians had good quality in this regard. Keywords: Communication, Talk, Healthcare team, Hospitalized children. *Corresponding Author: Zahra, Goodarzi. Lecturer, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran. E-mail: godarziz@sina.tums.ac.ir